Vehicle emissions and consumer information in car advertisements - Thomson George; Maher Anthony; Wilson Nick; Keall Michael (BMC, 2008)
Abstract Background The advertising of vehicles has been studied from a safety perspective but not in terms of vehicle air pollutants. We aimed to examine the content and trends of greenhouse gas emissions and air pollution-related information, in light passenger vehicle advertisements. Methods Content analysis of the two most popular current affairs magazines in New Zealand for the five year period 2001-2005 was undertaken (n = 514 advertisements). This was supplemented with vehicle data from official websites. Results The advertisements studied provided some information on fuel type (52%), and engine size (39%); but hardly any provided information on fuel efficiency (3%), or emissions (4%). Over the five-year period the reported engine size increased significantly, while fuel efficiency did not improve. For the vehicles advertised, for which relevant official website data could be obtained, the average "greenhouse rating" for carbon dioxide (CO2) emissions was 5.1, with a range from 0.5 to 8.5 (on a scale with 10 being the best and 0.5 being the most polluting). The average CO2 emissions were 50% higher than the average for cars made by European manufacturers. The average "air pollution" rating for the advertised vehicles was 5.4 (on the same 1-10 scale). The yearly averages for the "greenhouse" or "air pollution" ratings did not change significantly over the five-year period. One advertised hybrid vehicle had a fuel consumption that was under half the average (4.4 versus 9.9 L/100 km), as well as the best "greenhouse" and "air pollution" ratings. Conclusion To enhance informed consumer choice and to control greenhouse gas and air pollution emissions, governments should introduce regulations on the content of vehicle advertisements and marketing (as started by the European Union). Similar regulations are already in place for the marketing of many other consumer products.